Postpartum histoplasmosis in an HIV-negative woman: a case report and phylogenetic characterization by internal transcribed spacer region analysis - Lisandra Serra Damasceno; Antônio Mauro Barros Almeida Júnior; Bárbara de Oliveira Aguiar; Mauro de Medeiros Muniz; Marcos de Abreu Almeida; Rosely Maria Zancopé-Oliveira; Terezinha do Menino Jesus Silva Leitão (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract The present report describes the first case of postpartum disseminated histoplasmosis in a 24-year-old HIV-negative woman. On the tenth day after vaginal delivery, the patient presented with dyspnea, fever, hypotension, tachycardia, and painful hepatomegaly. Yeast-like Histoplasma capsulatum features were isolated in the buffy coat. The phylogenetic analysis demonstrated that the fungal isolate was similar to other H. capsulatum isolates identified in HIV patients from Ceará and Latin America. Thus, histoplasmosis development in individuals with transitory immunosuppression or during the period of immunological recovery should be carefully examined.